Antioxidant and α-glucosidase inhibitory ingredients identified from Jerusalem artichoke flowers. Issue 4 (16th February 2019) - Wang, Yan-Ming; Zhao, Jian-Qiang; Yang, Jun-Li; Idong, Pema Tsering; Mei, Li-Juan; Tao, Yan-Duo; Shi, Yan-Ping
Abstract: Jerusalem artichoke (JA, Helianthus tuberosus L.) has been researched extensively due to its wide range of uses, but there are limited studies on its flowers. In this study, we report the first detailed phytochemical study on JA flowers, which yielded 21 compounds. Compound4 was identified as a major water-soluble yellow pigment of JA flowers. In addition, the methanol extract of JA flowers and the isolates were evaluated for their antioxidant and α -glucosidase inhibitory activities. Among the tested compounds, compound13 showed the strongest ABTS + free radical scavenging activity with SC50 value of 2.30 ± 0.13 μg/mL, and compound6 showed most potent α -glucosidase inhibitory activity with inhibition rate of 60.0% ± 10.3% at a concentration of 250 μg/mL. Results showed that methanol extract of JA flowers exhibited antioxidant and α -glucosidase inhibitory activities which could be attributed to its phenolic ingredients including chlorogenic acid derivatives, flavonoids and phenols. Abstract :